Mathematical connection ability in solving hots questions on systems of linear equations in two variables material - Afriani, Diana; Machromah, Isnaeni Umi (Desimal: Jurnal Matematika, 2025)
In the world of mathematics education, mathematical connection skills played an important role, especially in dealing with Higher Order Thinking Skills (HOTS) type questions, where students were required to understand and solve problems well. However, in reality, many students faced difficulty in solving these problems. This research aimed to analyze junior high school students' mathematical connection abilities in solving HOTS questions on systems of linear equations in two variables material. The study used a descriptive method to understand the phenomenon being investigated. Data collection techniques included tests, which assessed specific aspects of student abilities, and interviews, which enabled the researchers to observe and analyze students' behavior in their natural context. The results indicated that students with high mathematical ability demonstrated connections that met all three indicators of mathematical connection, students with moderate mathematical ability fulfilled two indicators well, and students with low mathematical ability fulfilled only one indicator of mathematical connection adequately.